Effectiveness of using the shock wave in selected dysfunctions of the musculoskeletal system - Momot-Kuryło, Magdalena; Grzegorczyk, Michał (Journal of Education, Health and Sport, 2022)
Introduction In medicine, the shockwave was first used in the 1980s for lithotripsy [1]. Over time, new reports appeared about its positive impact on the human body, including on the musculoskeletal system. Nowadays it is successfully used in many fields of medicine. Shockwave is a relatively new method used in physiotherapy. More and more often it is used to treat musculoskeletal dysfunctions, incl. Patellar ligament enthesopathy, lateral epicondylitis of the humerus or heel spur. The studies conducted so far prove its high efficiency and low invasiveness [2,3]. From the point of view of physics, it is a mechanical wave characterized by a large change in pressure in a short time and a low frequency [4]. Objective of the work The aim of the study was to evaluate the effectiveness of the shock wave application in patients with patellar ligament enthesopathy, lateral epicondylitis of the humerus and heel spur. Material and methods The research was carried out in CM Luxmed, ul. Zwycięska 6a and CM MEDISPORT at ul. Łabędzia in Lublin in the period from 01/12/2020. until December 10, 2021 75 patients took part in them. 25 of them were diagnosed with patellar ligament enthesopathy, another 25 with lateral epicondylitis of the humerus. The remaining 25 people received shock wave treatments for the heel spur. Each respondent underwent 5 shock wave treatments. Before starting the research, the respondents were informed about the purpose of the research. Moreover, they were guaranteed anonymity. Results: Among the surveyed people, in general, 50.7% (n = 38) of all respondents were women, and 49.3% (n = 37) - men. 36% (n = 9) women and 64% (n = 16) men were among the respondents treated for lateral epicondylitis of the humerus. In the case of the jumper's knee, the study group consisted of 60% (n = 15) women and 40% (n = 10) men, while in the group of patients with the heel spur, women constituted 56% (n = 14), and men 44% (n = 11). Conclusions: Based on the research carried out, the following conclusions can be drawn: The application of the shock wave reduces pain among the respondents. The application of the shock wave reduces swelling in the treatment area. The application of the shock wave improves the mobility of the diseased joint. Shock wave treatments improve the functioning of patients in everyday life. Shock wave treatments improve the quality of professional work.